MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI TKJ SMK BINA TEKNOLOGI PURWOKERTO PADA MATERI MANAJEMEN BANDWIDTH MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Afif Nur Hidayat (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2020)
This study aims to: (1) Know the development process and (2) increase the critical thinking skills of class XI TKJ students of SMK Bina Teknologi Purwokerto on bandwidth management material.This research is a Classroom Action Research which was conducted from 27 October 2020 to 23 November 2020. The stages of the research consisted of planning, action, observation and reflection. The research was conducted in 3 cycles, each of which consisted of one meeting. The research instrument consisted of observation sheets and tests of students' critical thinking skills. Learning in this study uses the Problem Based Learning learning model. The action of data analysis used data from observations and the process of analyzing data from the test results of students' critical thinking skills.Before the implementation of the Problem Based Learning learning model for XI TKJ students, data was obtained with an average grade XI TKJ grade 54 and the completeness of students who had a score above 36% KKM. After applying the Problem Based Learning model in cycle 1, the class average increase to 60.04 and the completeness of students who have a score above the KKM is 44%. Then it has increased after cycle 2 with an average class score of 69.72 and completeness of students who have scores above the KKM 64%. Then it has increased after cycle 3 with an average class score of 76.72 and the completeness of students who have a score above the KKM of 80%. Thus it can be said that the application of the Problem Based Learning learning model can improve students' critical thinking skills.Keywords: critical thinking, problem based learning model, classroom action research,